Fundamentos econômicos e quantitativos no planejamento turístico - Rabahy, Wilson Abrahão (Revista Turismo em Análise, 1990)
The theory in which tourism planning is based emphasizes the importance of three factors in the development of the sector: social and economic, psycho-sociological and technical. The measurement of the effects of some of these factors and the construction of models for tourism forecastsare object of the econometric treatment. The particular use of econometricinvestigation methods of the tourism phenomenon is named theorometrics. The elaboration of a theorometric model for forecasts in the sector is based on scientific by theoretical statements of Mathematics and Statistics required by Econometrics. Experiments can be done after the construction of these models, and once tested and confirmed, they provide new basis for the tourism scientific knowledge and allow more realistic anallysis and forecasts of the phenomenon. Some of these theorometric experiments, as well as their utilization in a particular issue of the Brazilian tourism are, therefore, applied and their outputs confirm the validity of too scientific treatment, reducing the margin of error of the forecasts and funding better the economic policy decisions.